Special issue: ‘Literacy, language and social justice in the changing university’ - Thesen, Lucia; Jacobs, Cecilia; Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
In this special issue we share insights into how academics understand and research literacy and language in the context of calls for social justice rather than(or as well as) throughput and efficiency. This special issue comes about in the wake of a crucial moment in South African higher education, a moment of intense student led protest that has asked fundamental questions about what higher education is, who it is for, who it excludes. Not since the student led Soweto Uprising of 1976 have young people so insistently asked questions of the flawed educational inheritance that is coming their way. This questioning is not only taking place in South Africa but the local protests have an added urgency and meaning because of the historical context –a generation after apartheid, inequality is still sharply etched despite widening participation. Literacy and language are often implicated in this challenge to business-as-usual, raising questions about knowledge, pedagogy and taken-for-granted forms. It continues to be a crucial topic in this journal, and in critical approaches to teaching and learning in higher education, in South Africa in particular with its post-colonial context where English is in one way or another always a borrowed language, and writing in English carries with it profound dilemmas about identity and being.